2022
DOI: 10.3390/medicina58030441
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Immunogenicity of mRNA-Based COVID-19 Vaccine among Healthcare Workers: A Single-Centre Experience

Abstract: Background and Objectives: The safety and effectiveness of vaccines are among the key priorities in COVID-19 pandemic management. Moreover, evidence-based data regarding vaccine safety and immunogenicity can play an important role in building the trust of the community regarding vaccination. The aim of this study was to investigate the safety and immunogenicity of Pfizer-BioNTech vaccine among healthcare workers in one hospital, 21 days after first dose. Materials and Methods: This study was conducted in the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some vaccines are even associated with myocarditis, including mRNA vaccines [ 5 ]. One study demonstrated that, after the administration of the first mRNA vaccine dose, 53.6% of participants experienced at least one adverse event, the majority of which were local reactions [ 6 ]. The risk of experiencing adverse events has become one of the main reasons for anti-SARS-CoV-2 vaccination hesitancy among healthcare professionals around the world [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some vaccines are even associated with myocarditis, including mRNA vaccines [ 5 ]. One study demonstrated that, after the administration of the first mRNA vaccine dose, 53.6% of participants experienced at least one adverse event, the majority of which were local reactions [ 6 ]. The risk of experiencing adverse events has become one of the main reasons for anti-SARS-CoV-2 vaccination hesitancy among healthcare professionals around the world [ 7 ].…”
Section: Introductionmentioning
confidence: 99%